Faktor Penghambat Kantor Urusan Agama Kecamatan Biau Dalam Menanggulangi Masalah Perkawinan Poliandri Di Kabupaten Buol - Supratman, Supratman; Kasim, Nur Mohamad; Towadi, Mellisa (CV. ITTC INDONESIA, 2023)
Polyandry marriage is a form of marriage that is prohibited by Islam. This prohibition has been clearly stated in the Al-Qur'an and also the hadith of the Prophet. The scholars also agreed on its prohibition. This marriage also contradicts Law Number 1 of 1974 and article 40 of the Compilation of Islamic Law. However, in reality, polyandry marriages have occurred in Biau District, Buol Regency. The main problems that will be studied in this thesis research are as follows: The Role of the Biau District Office of Religious Affairs in Overcoming Polyandry Marriage Problems in Buol District. Empirical legal research that combines primary data obtained in the field, especially regarding, with primary data derived from primary legal materials, includes primary, secondary and tertiary data. The results of this study, the first is that polyandry marriages that occur in Biau District, Buol Regency are caused by ignorance of the guardian, also the will of the perpetrator himself, low level of knowledge, and also administrative factors which then make this forbidden marriage able to be registered and obtain a marriage book . And the role of the KUA itself is in conducting counseling and fostering the understanding of the people of Biau District, Buol Regency regarding the good and bad of polyandry marriages.